2022
DOI: 10.3390/microorganisms10010145
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Production of Antimicrobial Nanoparticles by Chlorella vulgaris and the Link to Its Loss of Viability

Abstract: Chlorella vulgaris from Al-Ahsa, KSA was proved to be an active silver and gold nanoparticle producer. Nanogold and nanosilver particles were characterized using UV-visible spectroscopy, Fourier-transform infrared spectroscopy, and scanning electronmicroscopy. Both nanoparticles were used in the antimicrobial bioassay. The two nanoparticles showed antibacterial activities, with the silver nanoparticles being the most effective. To investigate the argumentative nature of their biosynthesis (i.e., whether it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Several studies have reported the antibacterial activity of AgNPs, and AuNPs (Kuppusamy et al 2017 ; Beldjilali et al 2020 ; Herbin et al 2022 ). Moreover, recent studies supported that AgNPs have higher activity than AuNPs (Liu et al 2016 ; Aldayel et al 2022 ; Beck et al 2022 ), which can be explained by the different functional groups attributed to both nanoparticles upon the biosynthesis (Li et al 2018 ). Moreover, the alloy of the bi-metallic Au-AgNPs shows various promising applications in different fields, as many studies reported its higher reactivity compared to each of the nanoparticles (Emam et al 2017 ; Fang et al 2019 ; Ha Pham et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported the antibacterial activity of AgNPs, and AuNPs (Kuppusamy et al 2017 ; Beldjilali et al 2020 ; Herbin et al 2022 ). Moreover, recent studies supported that AgNPs have higher activity than AuNPs (Liu et al 2016 ; Aldayel et al 2022 ; Beck et al 2022 ), which can be explained by the different functional groups attributed to both nanoparticles upon the biosynthesis (Li et al 2018 ). Moreover, the alloy of the bi-metallic Au-AgNPs shows various promising applications in different fields, as many studies reported its higher reactivity compared to each of the nanoparticles (Emam et al 2017 ; Fang et al 2019 ; Ha Pham et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…In other studies, (just to mention a few of the works as examples) Soleimani and Habibi-Pirkoohi, 2017, Morowyat et al, 2023, and Aldayel et al, 2022 10,77,94 reported that AgNPs, ZnONPs, and AuNPs/AgNPs green-synthesized from C. vulgaris had antibacterial activity against Staphylococcus aureus, S. aureus/Enterococcus, E. coli/S. aureus, and Streptococcus sp., respectively.…”
Section: Biomedicalmentioning
confidence: 99%
“…These potentialities qualify microalgae as a promising source of raw material for the synthesis of various NPs. 76,77 In summary, microalgae often have remarkable advantages in terms of production efficiency, compositional uniformity, and environmental adaptability compared to vascular plants, making them promising candidates for NPs biosynthesis with various fields of application. 5…”
Section: Advantages Of the Green Synthesis Of Nps From Microalgae Vs ...mentioning
confidence: 99%
“…37-2-1), have also been shown to have antibacterial activity. Moreover, Chlorella vulgaris, as a nanofactory microalgae, was used for the synthesis of Ag and Au nanoparticles [ 75 ]. The two types of nanoparticles showed antibacterial activity toward Staphylococcus aureus , Streptococcus spp., and Escherichia coli.…”
Section: Green Synthesis Of Nanomaterialsmentioning
confidence: 99%